Prescription of Strong Opioids in Chronic Non-Cancer Pain in the Province of Valladolid (Spain) - Rodrigo Enríquez de Salamanca Gambara; Ana María Sierra Santos; Ana María Ruiz San Pedro; Federico Montero Cuadrado; Irene Muñoz León; Miguel Ángel Castro Villamor; Alicia Córdoba Romero; Ana María Del Olmo Tornero; Lucía Pérez Pérez; León Morales-Quezada (Life)
Background: Chronic non-cancer pain (CNCP) is one of the leading causes of disability. The use of strong opioids (SOs) in the management of CNCP is increasing, although evidence supporting their use remains limited. Primary care (PC) plays a key role in this context. Objectives: Our objectives were to determine the prevalence and profile of patients using SOs for CNCP in PC consultations in Valladolid in 2022, and to describe the consumption of SO prescribed for CNCP from 2020 to 2023. Methods: We conducted a descriptive and retrospective study using data extracted from the Pharmaceutical Consumption Information System of Castilla y León. Patients in Valladolid with SO use for more than three months due to CNCP were analyzed. Sociodemographic and clinical characteristics of these patients in 2022 were described. The number of defined daily doses (nº DDDs) and costs from 2020 to 2023 were analyzed. Results: A total of 3642 patients were included (0.7% of the population of Valladolid), 71.8% of whom were women. Of the patients, 62.4% were aged 70 or older, 39.8% lived in rural areas, and 9.9% resided in nursing homes. The most frequently prescribed SOs in nº DDDs were fentanyl and tapentadol. The highest consumption in nº DDDs was in patients who lived in nursing homes, were over 70 years old and were resident in rural areas. The number of DDDs from 2020 to 2023 for SOs in DCNO increased by 41%. Conclusions: In total, 0.7% of the population of Valladolid consumes SOs for CNCP, mostly women and people over 70 years old. The consumption of strong opioids in DDDs grew by 41% from 2020 to 2023.